Chinese economic development difference factors empirical study - Lihua Ma; Mingmei Sun; Huizhe Yan; Yufei Chen (PLoS ONE, 2025)
This article provides a detailed analysis and empirical support for the fiscal decentralization system, exploring its mechanisms in regulating the imbalance and insufficiency of regional economic development in China. The research found that fiscal decentralization, as a social governance tool, has a significant positive effect on narrowing the economic development gap between cities and addressing developmental disparities, particularly in the southern and vast inland regions of China. This effect provides important impetus for regional economic balance and comprehensive development. Secondly, mechanism testing revealed that technological support and the optimization of the administrative environment play crucial roles in promoting balanced regional economic development. By optimizing the industrial structure and strengthening the regulatory strategy for fiscal pressure, the positive impact of fiscal decentralization on economic development can be significantly enhanced. Furthermore, this study employs panel data threshold effect analysis to reveal that the level of tax competition moderates the effects of fiscal decentralization within a certain range, which in turn impacts the trajectory of economic development. These insights aim not only to leverage the fiscal decentralization system to alleviate and improve the uneven and inadequate economic development among regions in China and help achieve the goal of social governance, but also to provide a solid theoretical basis and practical guidance for the government in designing more precise and effective economic policies, which holds significant strategic importance and practical value.